Rapidly progressive dementia in Argentina: A multicentric study: Epidemiology / Prevalence, incidence, and outcomes of MCI and dementia. (7th December 2020) - Isa, Santiago; Calandri, Ismael Luis; Demey, Ignacio; Dorman, Guido; Couto, Blas; Vigo, Gabriela; Aleman, Alberto; Mellinger, Surai; Aldecoa, Mayra; Genovese, Osvaldo; Sanchez, Maria Pilar; O'Neill, Santiago; et al.
Abstract: Background: Rapidly progressive dementia (RPD) is a syndrome caused by different disease entities. Accurate diagnosis is crucial as numerous proportions of these diseases are highly treatable. There are few RPD series published in South America. Knowing regional data may be useful to establish specific diagnostic guidelines based on local information. The main study objectives are to describe the etiological diagnosis of patients with RPD in Argentina and to compare the clinical characteristics and data obtained from complementary studies among patients with Autoimmune Encephalitis (AE), Prion Diseases (PD), Neurodegenerative Diseases (ND) and Other Causes (OC). Method: A multicenter observational cross‐sectional study was performed with the information obtained from patients referred to the neurology department of the participant centers. Patients with RPD criteria (developing dementia in less than 24 months) were retrospectively included between Dec‐2001 and Jun‐2019. Based on International diagnostic criteria, patients were divided into: AE, PD, ND and OC. We compared baseline clinical data, complementary exams, MRI and serologic characteristics between groups. Parametric or non‐parametric statistic and multivariate analysis was used according to the sample distribution of the available data. Result: On a sample of 328 patients with a diagnosis of RPD, 54.87% were men (n=180) with a mean age of 60.78±5.57 years at admission. The diagnosis time for dementia was 4.06 (0.83–23.6) months. The three most frequent causes were AE 23.17% (n=76), ND 22.86% (n=75) and PD 15.85% (n = 52). In 15.85% of the patients the diagnosis remained unknown. When comparing AE, ND, PD and OC, statistically significant differences were observed in age (younger age for AE, p=0.0001), higher mortality for PD (p=0.0001) and larger time of evolution in ND (p=0.0001). In the PD group more behavioral symptoms (p = 0.002) and pathological electroencephalogram (p=0.001) were found. Conclusion: In accordance with similar series, autoimmune etiology was the more frequent cause. This is the first South American RPD multicentric study. These results might supply valuable data for the healthcare system and future epidemiological investigations more focused diagnostic guidelines.